Pengaruh Media Pembelajaran Ladders And Snakes (Ular Tangga) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Akidah Akhlak Di Kelas IV MI M (Madrasah Ibtidaiyah Muhammadiyah) 19 Sidokumpul Lamongan - Mahmudah, Siti; Suharsono (Jurnal Mahasiswa Pendidikan, 2021)
Ladders And Snakes learning media is part of cooperative learning that gives students experience to share knowledge both in groups and in other groups. The purpose of this study is to analyze whether there is an effect of Ladders And Snakes learning media on learning outcomes of Akidah Akhlak at MI Muhammadiyah 19 Sidokumpul Paciran Lamongan. The type of research is quantitative research with parametric statistical tests. The research location was at MI Muhammadiyah 19 Sidokumpul Paciran Lamongan. The population in this research were all students of class IV, consisted of 20 people with sample of 20 people taken using a sensus sampling technic. Data collection techniques in this study using observation, documentation and tests. The data analysis technique used is the T-test. Based on the results of hypothesis testing using a significance test (t-test) obtained t_count 5,104, then compared with t_table for a significant level of 5% (0.05) using a two-party test with dk = n-2 = 18 then obtained t_table of 2.101. it is known that t_count (5,105) > t_table (2,101), then Ho is rejected and Ha is accepted. It can be concluded that the Ladders And Snakes learning media (Ladders And Snakes) has a significant influence on the learning outcomes of Akidah Akhlak kleas IV MI Muhammadiyah 19 Sidukumpul Paciran Lamongan for the 2020/2021 academic year.